THE WELL-KNOWN, THE IGNORED THING AND WHAT WE NEED TO INVESTIGATE. FEDERAL DISTRICT, METROPOLITAN ZONE OF THE VALLEY OF MEXICO, CITY REGION OFTHE CENTER (Andamios, Revista de Investigación Social, 2004)
This paper presents a general outlook on the mainstream orientations that prevail nowadays in Mexico City studies. These orientations fail to recognize the functioning of the city as a totality, operating on the basis of a serious fragmentation of the object under study. The author holds that the Distrito Federal is only a part of a real city, formed by the metropolitan zone of the Valle de México. Because of this, it is necessary to develop these kinds of studies in a metropolitan scale or, at least, pu- tting these fragmentary studies in a general context. The article also de- als with some fields of research that the strategist should take into account for the structural change of the metropoli.